Visible-Light-Driven g-C3N4/TiO2 Based Heterojunction Nanocomposites for Photocatalytic Degradation of Organic Dyes in Wastewater: A Review - Sewnet, Agidew; Abebe, Mulualem; Asaithambi, Perumal; Alemayehu, Esayas (Air, soil and water research, 2022)
Water pollution by organic contaminants is one of the most severe issues confronting the world today as a result of the rapid increase of industrialization, urbanization, human population growth, and advances in agricultural technologies. Several attempts have been made to address global water pollution issues by utilizing conventional wastewater treatment technologies. However, conventional wastewater treatment methods have several limitations such as low efficiency, high operation costs, generation of secondary waste, require additional chemicals as oxidants and extra energy. Therefore, Heterogeneous photocatalysis has gained a lot of attention in the degradation of persistent organic pollutants because it combines high efficiency, environmental friendliness, cheap cost, and safety. Subsequently, the designing of novel nanocomposite photocatalysts with strong visible light-harvesting ability, efficient charge separation and transportation, and superb stability is imminently desired for wastewater treatment. Recently, the notion of combining g-C3N4 with TiO2 to design high photocatalytic performance heterojunction photoactive nanocomposites for organic pollutant degradation has received a lot of attention. Meanwhile, the construction of g-C3N4/TiO2-based heterojunction nanocomposites may enhance the ability of harvesting visible light, boost charge separation and transfer efficiency, and robust photocatalytic activity. Firstly, this review concisely explained the main sources of water pollution, as well as potential treatment approaches and the fundamental mechanism of heterogeneous photocatalysis. Subsequently, the details of properties, synthesis techniques, photoactivity modification strategies, and photocatalytic applications of g-C3N4, TiO2, and g-C3N4/TiO2 heterojunction photocatalysts are presented. Following that, the recent advances aimed at improving the photocatalytic performance of various types of visible-light-driven g-C3N4/TiO2 heterojunction photocatalysts for organic pollutant degradation in wastewater are presented in detail. Finally, some concluding remarks and perspectives on the challenges and opportunities for constructing different types of g-C3N4/TiO2-based heterostructured photocatalysts are presented.